(untitled) (African Journal of Biomedical Research, 2020)
Epilepsy is one of the least understood and most feared neurological disorders. It is associated with considerable stigma and discrimination, contributing to the immense psychosocial and emotional burden experienced by people living with epilepsy (PWE) particularly in developing countries. In order to fully understand the extent of this relationship, this study sought to assess the actual experience of discrimination, the degree of internalized stigma, and the perception (knowledge & attitude) of the general public towards epilepsy. Data on sociodemographic variables, internalized stigma and discrimination was collected from two groups of 103 eligible participants presenting at the Neurology and General outpatient clinics of the University College Hospital, Ibadan, using two structured interviewer-administered questionnaires. A high proportion of PWE (n=24, 57.1%) reported severe internalized stigma despite majority (76.9%) reporting not being discriminated against. Thirty-two respondents (56.1%) reported that they would not employ or work with someone known to have epilepsy. A considerable number of people (n=41, 82%) reported that they would help PWE away from danger during a seizure and 46 respondents claimed they were going to call for help, while 15 (of 42 respondents) reported that they would run away. While this study revealed quite a number of positives, it is apparent that there still exists a lot of ignorance and misconceptions about epilepsy and significant improvement is still needed with regards to addressing the stigma of epilepsy and the public attitude towards epilepsy and PWE